Highly diluted medication reduces tissue parasitism and inflammation in mice infected by Trypanosoma cruzi. Issue 2 (May 2016) - Lopes, Carina Ribeiro; Falkowski, Gislaine Janaina Sanchez; Brustolin, Camila Fernanda; Massini, Paula Fernanda; Ferreira, Érika Cristina; Moreira, Neide Martins; Aleixo, Denise Lessa; Kaneshima, Edilson Nobuyoshi; de Araújo, Silvana Marques
Abstract : Aim: To evaluate the effects of Kalium causticum, Conium maculatum, and Lycopodium clavatum 13cH in mice infected by Trypanosoma cruzi. Materials and methods: In a blind, controlled, randomized study, 102 male Swiss mice, 8 weeks old, were inoculated with 1400 trypomastigotes of the Y strain of T. cruzi and distributed into the following groups: CI (treated with 7% hydroalcoholic solution), Ca (treated with Kalium causticum 13cH), Co (treated with Conium maculatum 13cH), and Ly (treated with Lycopodium clavatum 13cH). The treatments were performed 48 h before and 48, 96, and 144 h after infection. The medication was repertorized and prepared in 13cH, according to Brazilian Homeopathic Pharmacopoeia. The following parameters were evaluated: infectivity, prepatent period, parasitemia peak, total parasitemia, tissue tropism, inflammatory infiltrate, and survival. Statistical analysis was conduced considering 5% of significance. Results: The prepatent period was greater in the Ly group than in the CI group ( p  = 0.02). The number of trypomastigotes on the 8th day after infection was lower in the Ca group than in the CI group ( p  < 0.05). Total parasitemia was significantly lower in the Ca, Co, and Ly groups than in the CI group. On the 12th day after infection, the Ca, Co, and Ly groups had fewer nests and amastigotes/nest in the heart than the CI group ( p  < 0.05). Decreases in the number of nests and amastigotes in the intestine were observed in the Ly group compared with the CI group ( p  < 0.05). In the liver (day 12), Ly significantly prevented the formation of inflammatory foci compared with the other groups. In skeletal muscle, Co and Ly decreased the formation of inflammatory foci compared with CI ( p  < 0.05). Ly afforded greater animal survival compared with CI, Ca, and Co ( p  < 0.05). The animals in the Co group died prematurely compared with the CI group ( p  = 0.03). Conclusions: Ly with 13cH potency had significantly more benefits in the treatment of mice infected with T. cruzi, reducing the number of blood parasites, amastigote nests in tissue, and the number of amastigotes per nest and increasing animal survival. Highlights: Homeopathic medicines decrease parasitemia in T. cruzi infection. Homeopathic medicines decrease tissue parasitism/inflammation in T. cruzi infection. Lycopodium clavatum afforded greater survival in animals infected by T. cruzi .